An open-source remote heart rate imaging method with practical apparatus and algorithms - van der Kooij, Koen M.; Naber, Marnix (Behavior research methods, 2019)
Recent developments in computer science and digital image processing have enabled the extraction of an individual’s heart pulsations from pixel changes in recorded video images of human skin surfaces. This method is termed remote photoplethysmography (rPPG) and can be achieved with consumer-level cameras (e.g., a webcam or mobile camera). The goal of the present publication is two-fold. First, we aim to organize future rPPG software developments in a tractable and nontechnical manner, such that the public gains access to a basic open-source rPPG code, comes to understand its utility, and can follow its most recent progressions. The second goal is to investigate rPPG’s accuracy in detecting heart rates from the skin surfaces of several body parts after physical exercise and under ambient lighting conditions with a consumer-level camera. We report that rPPG is highly accurate when the camera is aimed at facial skin tissue, but that the heart rate recordings from wrist regions are less reliable, and recordings from the calves are unreliable. Facial rPPG remained accurate despite the high heart rates after exercise. The proposed research procedures and the experimental findings provide guidelines for future studies on rPPG.